2010
DOI: 10.1097/spc.0b013e328339920d
|View full text |Cite
|
Sign up to set email alerts
|

Management of dyspnea in advanced lung cancer: recent data and emerging concepts

Abstract: This study reviews several interesting advances in the area of dyspnea with respect to symptom assessment and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…A recent review concluded that few definitive data are available evaluating the effectiveness of dyspnea interventions, and that randomized controlled trials are needed. 59 Other reviews have determined that data are sufficient to make treatment recommendations. 57,60 Pharmacologic interventions include opioids or benzodiazapines.…”
Section: Palliative Care Interventionsmentioning
confidence: 99%
“…A recent review concluded that few definitive data are available evaluating the effectiveness of dyspnea interventions, and that randomized controlled trials are needed. 59 Other reviews have determined that data are sufficient to make treatment recommendations. 57,60 Pharmacologic interventions include opioids or benzodiazapines.…”
Section: Palliative Care Interventionsmentioning
confidence: 99%
“…(2010), Synthesis of systemic reviews -breathlessness in respiratory illness[8]; B, Roberston-Malt (2010), Synthesis of systematic reviews -asthma[9]; C, Simon et al(2010), Systemic review -benzodiazepines in malignant and nonmalignant disease [11 ]; D, Hunt et al, Systemic review -heliox during exercise in COPD [10]; E, Thomas et al (2010), Systemic review -COPD [12]; F, Alifano et al (2010), Narrative review -COPD [13]; G, Davidson and Currow (2010), Narrative review -refractory dyspnoea multiple diseases [14 ]; H, Gibson et al (2010), Narrative review -acupuncture for respiratory disorders [15]; I, Johnson and Oxenbury (2010), Narrative review -chronic heart failure [16 ]; J, McMurray (2010), Narrative review -systolic heart failure [17]; K, Sajkov et al (2010), Narrative review -pulmonary hypertension [18 ]; L, Shannon (2010), Narrative review -lung cancer [19]; M, Riario-Sforza et al (2010), Narrative review -COPD [20]; N, Ryerson et al (2010), Narrative reviewinterstitial lung disease [21 ]; O. Mahler et al (2010), Consensus statement -advanced lung or heart disease[23 ]; P, Xue and Abernethy (2010), Narrative review -advanced lung cancer[22].…”
mentioning
confidence: 99%
“…Dyspnea is a distressing symptom that is highly prevalent among patients with LC 4 - 8 ; mitigating this symptom is a high priority and a clear unmet need. In this pilot study, we demonstrated successful recruitment and retention to a study of acupuncture for dyspnea in LC.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 Dyspnea is present in up to 87% of patients with LC and has a profound impact on quality of life and survival. 4 - 8 The existing literature is sparse on interventions to improve dyspnea for patients with LC. 9 Physicians also appear to treat the dyspnea associated with LC less aggressively than they do dyspnea associated with chronic lung disease.…”
Section: Introductionmentioning
confidence: 99%